Perspectives on postindustrial society : (University of Tokyo Press, 1970)
This book focuses its attention on one of the crurcial sectors in the economic development of Asia, discussing pass and current trends in agricultural development, problem areas in the production of particular crops, and the development of agriculture-related industries in the developing member nations of the Asian Development Bank.